A novel methodology and strategy to detect low molecular aldehydes in beer based on charged microdroplet driving online derivatization and high resolution mass spectrometry. (30th July 2022) - Peng, Zifang; Luo, Yake; Song, Chenchen; Zhang, Yanhao; Sun, Shihao; Yu, Ajuan; Zhang, Wenfen; Zhao, Wuduo; Zhang, Shusheng; Xie, Jianping
Graphical abstract: Highlights: A novel online derivatization strategy was development to detect low molecular aldehydes based on the high-speed reaction accelerated in microdroplet. The novel method achieved more simple and rapid aldehydes' analysis without any chromatographic separation and sample pre-treatments than previous works. Different aldehydes in beer were successfully determined by this new analytical strategy. Abstract: The concentration of aldehydes is one of the important indicators in the food quality and safety. To efficiently analyze the four aldehydes (methanal, ethanal, propanal and n -butanal) in beer, charged microdroplet driving online derivatization apparatus coupled with high resolution mass spectrometry was firstly developed. Utilizing the high-speed reaction accelerated by microdroplets, the offline derivative of aldehydes with 2, 4-dinitrophenylhydrazine in bulk was transferred into online derivatization. The developed method featured acceptable linearities (R 2  ≥ 0.95), high sensitivities (LODs at ng mL −1 level) and qualified precisions (RSDs ≤ 8.4 %) for target compounds. Four aldehydes with trace amount were successfully determined in beer. The results indicated that the novel online analytical strategy did not require complex sample preparation and could conduct simple, rapid, sensitive detection of small molecule aldehydes with high throughput in beer or even other food samples.